Przyjaźń Stanisława Wygodzkiego z Władysławem Broniewskim w świetle dokumentów i egodokumentów (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The aim of this article is to describe the friendship of two Polish poets: Stanisław Wygodzki and Władysław Broniewski, and to assess its influence on the formation of the younger poet’s ideological attitudes and literary workshop. The research used archival sources: correspondence exchanged between the poets, Wygodzki’s e-documents, press materials published in Poland and Israel, and recordings of the author’s interviews with Irena Wygodzka. Methodologically, content analysis and reconstruction of the socio-political contexts of the inter-war and post-war period were used. Particular attention was paid to Broniewski’s mentoring function – the way of formulating critical remarks and workshop corrections was analysed. The article shows that the friendship discussed was a key factor in Wygodzki’s poetic development, creating a model of literary dialogue and social involvement, the echo of which can be seen in the later works of both authors.